Dispersion of Co/CNTs via strong electrostatic adsorption method: Thermal treatment effect - Akbarzadeh, O. (American Institute of Physics Inc., 2015)
The effect of different thermal treatment temperature on the structure of multi-walled carbon nanotubes (MWCNTs) and Co particle dispersion on CNTs support is studied using Strong electrostatic adsorption (SEA) method. The samples tested by N 2 -adsorption, field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). N 2 -adsorption results showed BET surface area increased using thermal treatment and TEM images showed that increasing the thermal treatment temperature lead to flaky CNTs and defects introduced on the outer surface and Co particle dispersion increased. Â© 2015 AIP Publishing LLC.